DINAMIKA GERAKAN SALAFI DAN PARADOKS KOSMOPOLITANISME ISLAM: PROBLEMA TERMINOLOGIS, SEJARAH DAN AJARAN - Muhammad Zainal Abidin (Universitas Islam Negeri Antasari Banjarmasin, 2022)
AbstractThis paper is intended to examine the salafi movement in the context of the paradox of Islamic cosmopolitanism, which is seen in the terminological, historical and teaching aspects. The spirit of the Islamic resurgence that emerged at the time of entering the 15th century of Hijry, has taken the new spirit for returning to Islam, proud of being Muslim, and wake up awareness that the lagging Islam is caused by Muslims which leaving their religion. The problem has arisen, that the spirit to return to the Islam is accompanied by the emergence of a transnational Islamic movement in the Sunni world called salafi or wahhabi. The spirit of the salafi (wahabi) teaching is the purification of Islamic teachings from what the called as shirk and bid'ah. Islam with the mission of its rahmatan lil’alamin, has the strong connection with the spirit of cosmopolitanism, however it has been reduced by the existence of narrow salafi understanding. Some of the paradoxes that emerge are: 1) Transnational Islamic Movement, which ignores locality; 2) Receive the modernity (hadatsah) and reject the tradition (turats); and 3) Receive the text and reject the reason (logic).Keywords: Cosmopolitanism; Islam; Salafi; Paradox. AbstrakTulisan ini dimaksudkan untuk menelaah gerakan salafi dalam konteks paradoks kosmopolitanisme Islam, yang dilihat pada aspek terminologis, sejarah dan ajaran. Semangat Kebangkitan Islam yang muncul pada saat memasuki abad ke-15 Hijriyah, telah melahirkan semangat baru untuk kembali kepada Islam dan rasa bangga menjadi muslim, dan kesadaran bahwa penyebab ketertinggalan Islam adalah karena umat Islam meninggalkan agamanya. Persoalannya menjadi muncul, bahwa ghirah untuk kembali kepada Islam tersebut dibarengi dengan munculnya gerakan Islam transnasional di dunia sunni yang disebut salafi atau wahabi. Spirit dari ajaran salafi (wahabi) ini adalah purifikasi ajaran Islam dari apa yang disebut sebagai syirik dan bid’ah. Islam dengan misi rahmatan lil’alaminnya, sesuai dengan semangat kosmopolitanismenya, pada gilirannya menjadi tereduksi dengan paham salafi ini. Beberapa paradoks yang muncul adalah: 1) Gerakan Islam transnasional, yang mengabaikan lokalitas; 2) Menerima hadatsah (modernitas), menolak turats (tradisi); dan 3) Menerima teks, menolak nalar (logika). Kata Kunci: Islam; Kosmopolitanisme; Salafi; Paradox.